Practice reflection learning: work experience in planner education. (19th October 2016) - Wight, Ian; Kellett, Jon; Pieters, Johannes (Hans)
Abstract: This paper reports findings from textual analysis of the journals submitted by students who undertook the 2013 Planning Field Placement Course for the undergraduate degree of Urban and Regional Planning at the University of South Australia. We discuss the extent to which the reflective narratives contained in journal assignments demonstrate student expectations about the goals of work experience and their relative focus on descriptive versus reflective dimensions of work experience learning. We conclude that whilst the learning is quite significant, the extent of reflection on critical issues of professionalism is limited. Different perspectives on practice, reflection and learning seem to be in play, with possibly too much of a silo/solo approach to each. We end with some reflections on the implications for pedagogical practice in relation to work experience programming.